A review of aspects of hydrological sciences research in Africa over the past decade - (:unkn) unknown (My University, 2015)
This review assesses the potential of the African continent to contribute to the three main targets of the new science decade of IAHS (Panta Rhei): understanding, estimation and prediction, and science in practice. The continent has an extremely diverse climate and physical environment, and is faced with many problems in the interaction between hydrology and society. While inadequate financial and institutional resources often constrain the pursuit of high-level scientific research, there is substantial hydrological research capacity within Africa. The topics covered over the past decade have partly anticipated some of the research themes adopted as part of the Panta Rhei initiative. African hydrological scientists should therefore be in a better position to make future contributions, largely because their research is already grounded in applications linked to societal needs. Some of the papers reviewed and included in the special issue of Hydrological Sciences Journal introduced in this paper reflect international partnerships, while others reflect emerging partnerships between institutions within Africa. Editor M Acreman
Keywords: African Research